Contextualizing leaders' interpretations of proactive followership. (14th December 2015) - Benson, Alex J.; Hardy, James; Eys, Mark
Summary: Although proactive followership behavior is often viewed as instrumental to group success, leaders do not always respond favorably to the actions of overly eager followers. Guided by a constructivist perspective, we investigated how interpretations of followership differ across the settings in which acts of leadership and followership emerge. In thematically analyzing data from semi‐structured interviews with leaders of high‐performing teams, we depict how the construal of follower behaviors relates to various contextual factors underscoring leader–follower interactions. Prototypical characteristics were described in relation to ideal followership (i.e., active independent thought, ability to process self‐related information accurately, collective orientation, and relational transparency). However, proactive followership behaviors were subject to the situational and relational demands that were salient during leader–follower interactions. Notably, the presence of third‐party observers, the demands of the task, stage in the decision‐making process, suitability of the targeted issue, and relational dynamics influenced which follower behaviors were viewed as appropriate from the leader's perspective. These findings provide insight into when leaders are more likely to endorse proactive followership, suggesting that proactive followership requires an awareness of how to calibrate one's actions in accordance with prevailing circumstances. Copyright © 2015 John Wiley & Sons, Ltd.